2021
DOI: 10.4081/ijfs.2021.9974
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in vacuum packages of frozen and glazed icefish (<em>Neosalanx</em> spp.): A freshwater fish intended for human consumption

Abstract: It is widely accepted that human is exposed to microplastics through food consumption, however data occurrence in foodstuffs are still little and basically limited to seafood. In this study, the presence of microplastics was investigated in icefish (Neosalanx spp.) samples sourced from various mass-market retailers in Italy, supplied as frozen, glazed and vacuum-packed product. Icefish is a small freshwater fish widely imported in Europe from China as surrogate of other fish species subjected to commercial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, since the entry into force of the Council Regulation (EC) No 1967/2006, concerning management measures for the sustainable exploitation of fishery resources in the Mediterranean Sea, the “special forms of fishing” have been banned with few exemption for “rossetto” [ 58 ]. These restrictive measures on fishing together with the globalization of the fish trade, have opened the market to the arrival of species from foreing fishery areas, of less commercial value, which filled the void left by the banned species traditionally consumed in the Mediterranean area: this was the case of Neosalanx species or icefish, small freshwater fish species, widely imported in Italy from China as frozen product [ 59 , 60 ]. The fraudulent substitution of “bianchetto” by icefish has been already reported in Italy by Armani et al [ 53 ] who used a fragment of the mitochondrial cyt b gene as molecular marker and by Guerriero et al [ 54 ] who applied a PCR-RFLP analysis of a partial fragment of the mitochondrial 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the entry into force of the Council Regulation (EC) No 1967/2006, concerning management measures for the sustainable exploitation of fishery resources in the Mediterranean Sea, the “special forms of fishing” have been banned with few exemption for “rossetto” [ 58 ]. These restrictive measures on fishing together with the globalization of the fish trade, have opened the market to the arrival of species from foreing fishery areas, of less commercial value, which filled the void left by the banned species traditionally consumed in the Mediterranean area: this was the case of Neosalanx species or icefish, small freshwater fish species, widely imported in Italy from China as frozen product [ 59 , 60 ]. The fraudulent substitution of “bianchetto” by icefish has been already reported in Italy by Armani et al [ 53 ] who used a fragment of the mitochondrial cyt b gene as molecular marker and by Guerriero et al [ 54 ] who applied a PCR-RFLP analysis of a partial fragment of the mitochondrial 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…All studies on seafood used a mode of IR spectroscopy as the analytical technique. Most (50%) used micro-FT-IR, [62][63][64][65] almost 38% used ATR FT-IR, [82][83][84] and one study (12.5%) did not specify the mode of FT-IR. 85 Less than half the studies reported the spectral range analyzed.…”
Section: Drinking Water and Beveragesmentioning
confidence: 99%
“…62,63,84 Two studies adopting micro-FT-IR specified using transmittance mode. 63,65 Of the studies classifying spectra with a commercial library, 80% used an HQI > 70%, [63][64][65]84 whilst one used a commercial library but did not specify the HQI used 62 and one specified an HQI (>60%) but not specifically the use of a library. 82 Of the studies using ATR FT-IR to analyze seafood samples for microplastic, average microplastic abundances of 2.52 ± 1.1 microplastic particles mussel −1 from the Boka Kotorska Bay of the Adriatic Sea were found.…”
Section: Drinking Water and Beveragesmentioning
confidence: 99%
“… 28 Ingestion is believed to be the most common route of MPs exposure. 4 9 , 29 32 MP exposure in rats, 33 mice, 34 , 35 and zebrafish 36 , 37 models has been shown to lead to gut microbiota dysbiosis. Gut dysbiosis is linked to numerous inflammatory and metabolic diseases, 38 43 and studies in zebrafish exposed to MPs have been shown to induce intestinal injury and inflammation.…”
Section: Introductionmentioning
confidence: 99%